Retrospective of DIET process for enhanced biogas production during anaerobic digestion of thermal/chemically pretreated waste activated sludge - Almegbl, Abdulaziz Mohammed; Rahmani, Ali Mohammad; Kamal, Kamaluddin; Munshi, Faris Mohammad A.; Khursheed, Abbas; Ali, Muntjeer; Khursheed, Anwar (Frontiers in Environmental Engineering, 2025)
Hydrolysis of recalcitrant organic waste such as lignocellulosic biomass and waste-activated sludge (WAS) is a rate-limited step in anaerobic digestion (AD) due to the chemical and physical barriers that can be diminished by pretreatment of the waste. However, for readily biodegradable, soluble organics or already hydrolyzed organics, acetogenesis and methanogenesis become the rate-limiting steps owing to the discrepancy in the syntrophic relationship of the inter-microbial matrix. Enhancing the syntrophic relation of VFA oxidizing bacteria and hydrogenotrophic methanogens via direct interspecies electron transfer (DIET) is vital for enhanced and efficient bio-methanation. DIET changes the metabolic pathways, which can be evidenced by microbial diversity, abundance, and associated enzymes. The stimulation of DIET can enhance biogas production and methane content and enhance VFA and ammonia-stressed digesters. The conductive materials for DIET in AD should be non-hazardous, chemically stable, cheap, recyclable, non-reactive, porous, conductive, microbe-friendly, and provide a large surface area. DIET stimulation and optimization via sustainable materials for high organic wastes are the future research areas that need comprehensive exploration.